Improving the Commercial Value of the ‘Calçot’ (Allium cepa L.) Landrace: Influence of Genetic and Environmental Factors in Chemical Composition and Sensory Attributes - Sans, Silvia; Casals, Joan; Simó, Joan (Frontiers in Plant Science, 2018)
Landraces are considered valuable for their close ties to local cultures, adaptation to low inputs, and quality. ‘Calçots’ are the immature floral stems of second-year sprouts of onions from the ‘Blanca Tardana de Lleida’ landrace. ‘Calçots’ grown in their traditional area of cultivation have been awarded Protected Geographic Indication (PGI) ‘Calçot de Valls’ from the European Union. Despite annual sales of about €15 million, ‘calçot’ germplasm and cultivation methods are under-researched. This study aimed to estimate the influence of genetic and environmental factors in the chemical and sensory characteristics of ‘calçots’ to enable strategies to improve their commercial value to be devised. To this end, we tested the landrace and three new, more productive varieties derived from the landrace in experiments conducted over two seasons in six locations (within and outside the PGI zone), using two planting dates and two harvesting times. The results point to a major environmental influence in the quality of ‘calçots.’ The analysis of variance found all factors related with environmental influence were significant in most chemical traits considered (dry matter content, soluble solids content, pH, titratable acidity, and ash content), while the variety factor was significant only for titratable acidity. In sensory analyses, the variety factor and all the environmental factors had significant effects in all sensory traits recorded (sweetness, fiber perception, and off-flavors). In both chemical and sensory traits, most significant interactions involved the environmental factors. The negative correlation found between sweetness and fiber perception and off-flavors suggests that additional selection can bring ‘calçots’ closer to the sensory ideotype. Although clearly more productive, the new ‘calçot’ varieties maintain the chemical composition and sensory value of the landrace. Thus, fine-tuning the cultivation and/or breeding of the landrace for both yield and quality seem viable approaches to obtaining better commercial products.